Judicial review of Industrial Court awards: its blemish and proposed reform - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2010)
This article highlights the drawbacks of contesting awards of the Industrial Court in the civil courts by way of judicial review. It is contended that the existing mechanism for challenging awards of the Industrial Court by way of judicial review defeats the objectives of the Industrial Relations Act 1967 (IRA) to ensure the speedy disposal of industrial disputes. Apart from the inordinate or unwarranted delay in the civil courts, the costs of litigation are immense with the workers having to bear the financial burden and end up suffering themselves. Further, the article will also elucidate the fusion of the common law master and servant principles by the civil courts into the industrial jurisprudence. The civil courts are accustomed with the common law master and servant principle, which is based on legal justice.